Biportal Endoscopic Transforaminal Lumbar Interbody Fusion for Two-Level Fusion: Hemodynamic Profiles and Early Clinical Outcomes Compared with Tubular MIS and Open Approaches - Tae Hoon Kang; Byungjun Kang; Geumho Lee; Jeongwoon Han; Seokin Jang; Minjoon Cho; Jung-Man Lee; Jae Hyup Lee (Journal of Clinical Medicine, 2026)
Background/Objectives: Biportal endoscopic (BE) surgery is increasingly used for transforaminal lumbar interbody fusion (TLIF), but its hemodynamic profile and early recovery in two-level fusion remain undefined relative to tubular minimally invasive surgery (MIS) and open approaches. We compared the hemodynamic burden and early functional recovery among BE-, MIS-, and open two-level TLIF. Methods: In this retrospective single-center study of three sequential, non-contemporaneous cohorts, 96 patients undergoing two-level (L2–S1) TLIF (BE, n = 22; MIS, n = 39; open, n = 35) were analyzed. The single primary endpoint was transfusion-corrected total blood loss (corrected TBL), derived from hematocrit changes. Secondary endpoints were intraoperative estimated blood loss (EBL), drainage, allogeneic transfusion, hidden blood loss (HBL), complications, and the Numeric Rating Scale(NRS), Oswestry Disability Index (ODI), and Functional Rating Index (FRI) at 3 months. Effect sizes with 95% confidence intervals (CIs) are reported alongside p-values. Results: Corrected TBL was highest in open TLIF (2.07 ± 0.86 L) versus BE-TLIF (1.36 ± 0.54 L; mean difference −0.71 L, 95% CI −1.09 to −0.34) and MIS-TLIF (1.53 ± 0.50 L; −0.55 L, −0.88 to −0.21), whereas BE- and MIS-TLIF were comparable (−0.17 L, −0.45 to 0.12). Transfusion was required in 13.6%, 20.5%, and 60.0%, respectively (p < 0.001), with no difference between the minimally invasive groups. Intraoperative EBL was lower in BE-TLIF than in MIS-TLIF (−226.8 mL, −395.3 to −58.2). HBL was lowest in open TLIF (p = 0.030), reflecting its far larger drainage volume. At 3 months, BE-TLIF showed greater FRI improvement than MIS-TLIF (−3.97, −7.04 to −0.90); for ODI, BE-TLIF exceeded open TLIF but not MIS-TLIF. Wound problems (11.4%) and delirium (22.9%) occurred only or most often after open TLIF. Conclusions: In two-level fusion, BE-TLIF was associated with a lower overall hemodynamic burden and transfusion requirement than open TLIF, while corrected TBL was comparable between BE- and MIS-TLIF. Given the non-contemporaneous cohorts, baseline imbalances, limited sample size, and potential residual confounding, these findings should be considered hypothesis-generating and require confirmation in prospective or contemporaneously controlled studies.